Understanding the complexities of technological penetration and globalisation on labour market performance: The role of complementary policies - Abiola John Asaleye; Rufaro Garidzirai (Journal of Open Innovation: Technology, Market and Complexity)
Understanding the impact of technological penetration and globalisation on wage differentials and employment is crucial for developing countries aiming for sustainable economic growth and reduced unemployment rates. This study investigates these effects in the Southern African Development Community. It also examines the role of complementary policies, such as financial development and human capital, and their interactive effects with technological penetration on wages and employment. The study employs panel fully modified least squares, dynamic least squares, and Driscoll-Kraay's standard error as a robustness check. Results indicate that technological penetration, financial development, and the interactive effect of human capital and technological penetration negatively affect employment. Conversely, globalisation and the interactive effect of financial development and technological penetration positively influence employment. Technological penetration is insignificant in the wage equation, while human capital, globalisation, and financial development are associated with wage increases. The interactive effect of technological penetration and human capital is not significant, and the interactive effect of financial development and technological penetration negatively impacts wages. Based on the findings, the study recommends enhancing financial development and human capital while carefully managing technological integration to navigate the complexities of technological and global economic integration to maximise employment and wage benefits.